“a” for architecture an alternative book: design thesis folio 2007 - Syed Ariffin, Ahmad Iskandar (Penerbit UTM, 2008)
This book contains several chapters like section a, acknowledgement, foreword by dean of faculty, foreword by head of department/ thesis coordinator, foreword by chief editor. content in section b environmental unit, article : students perspective on sustainable tropical architectural ideas, the tropical shopping mall, passive solar design in apartment, environment responsive building envelope, breathing architecture – passive ventilated apartment, resort for Batu Ferringhi, Penang, housing and community unit, article : the development of the Wilayah Pembangunan Iskandar: harmony, sustainability and survivability of building design and city planning, Filipino community complex.